PREFERRED LEARNING STYLES AND SOFT SKILLS: THE MODERATING IMPACT OF GENDER AND RESIDENCE AREA - Kogilavani a/p Apadore; Ku Nur Ilyani Binti Ku Abd Aziz; Zam Zuriyati Mohamad; Meenah Ramasamy; Yamuna Rani Palanimally (Journal of Islamic, Social, Economics and Development, 2021)
This study aims to achieve three objectives. First, to determine the preferred learning styles for final year undergraduate accounting students. Second, to examine the effect of learning styles on soft skills. Third, to test whether gender and geographical residence area act as a moderator on the relationship between learning styles and soft skills. The preferred learning styles consist of visual, auditory and kinaesthetic while students’ soft skills consist of communication skill and critical thinking. Fleming’s Theory of Learning Style has been applied as the underlying theory. 300 undergraduate accounting students participated in this study. Barsch’s Learning Styles Inventory and Malaysian Soft Skills Scale were used to measure students’ learning styles and soft skills attainment level respectively. Partial least square structural equation modelling was executed to accomplish the objectives of this study. The result shows that the most preferred learning style is visual. All learning styles are statistically significant on soft skills. The Geographic residence area strengthens the influence of visual learning style on soft skills. This study contributes to the development in accounting education, lecturers’ teaching approach and student employability. Theoretically, this study offers a new path in the education research area by connecting learning styles and soft skills